The price of power: Valuing the controlling position of owner–managers in French IPO firms - Roosenboom, Peter; Schramade, Willem (Journal of Corporate Finance, 2006)
Going public often creates an agency conflict between the owner–manager and minority shareholders. This problem is especially severe in countries with poor legal investor protection, such as France. We examine the controlling position of owner–managers in French initial public offering (IPO) firms. We find that investors anticipate the increased agency conflict associated with a lock on control and lower firm value when the owner–manager is more powerful. Shareholder agreements in which the owner–manager agrees to share control with other pre-IPO owners enhance firm value. We also report that higher cash flow ownership by the owner–manager is positively related to firm value when he is not in full control. Finally, we document that the large (non-pecuniary) private benefits of control in France may motivate owner–managers to retain control after the IPO.